2012
DOI: 10.1073/pnas.1201583109
|View full text |Cite
|
Sign up to set email alerts
|

Wnt ligands signal in a cooperative manner to promote foregut organogenesis

Abstract: Endoderm-mesenchyme cross-talk is a central process in the development of foregut-derived organs. How signaling pathways integrate the activity of multiple ligands to guide organ development is poorly understood. We show that two Wnt ligands, Wnt2 and Wnt7b, cooperatively induce Wnt signaling without affecting the stabilization of the Wnt canonical effector β-catenin despite it being necessary for Wnt2-Wnt7b cooperativity. Wnt2-Wnt7b cooperation is specific for mesenchymal cell lineages and the combined loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…It has been reported that the β-catenin pathway is involved in the proximal-distal specification of lung epithelium by suppressing the expression of Sox2, a proximal airway marker (Hashimoto et al, 2012;Miller et al, 2012). In lung epithelium culture, CHIR99021 treatment decreased and increased mRNA levels of Sox2 and the distal progenitor marker SOX9 (Chang et al, 2013), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the β-catenin pathway is involved in the proximal-distal specification of lung epithelium by suppressing the expression of Sox2, a proximal airway marker (Hashimoto et al, 2012;Miller et al, 2012). In lung epithelium culture, CHIR99021 treatment decreased and increased mRNA levels of Sox2 and the distal progenitor marker SOX9 (Chang et al, 2013), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt2 and Wnt7b are cooperatively required for the mesenchymal β-catenin pathway in cultured cell lines and their simultaneous knockout causes defects in branching morphogenesis and proximal-distal specification (Miller et al, 2012). The β-catenin pathway is consistently activated in the distal endodermal tip and surrounding mesenchyme during the early stage of lung development, as observed in a reporter gene-expressing murine model (Al Alam et al, 2011), and is required for branching morphogenesis (De Langhe et al, 2005;Miller et al, 2012) as well as distal progenitor maintenance (Mucenski et al, 2003). Although these studies reveal the importance of Wnt signaling in lung development, it remains unclear how the β-catenin pathway is involved in epithelial cell morphogenesis during lung development.…”
Section: Introductionmentioning
confidence: 99%
“…There is an interesting explanation of noncanonical Wnts inducing canonical Wnt signaling: multiple Wnts might act in a combination [27,28]. In fact, the canonical Wnt, Wnt7b was also shown to cooperate with Wnt2 to promote foregut organogenesis [29]. All these complex interactions between Wnt ligands might lead to different observations, in some cases contradictory.…”
mentioning
confidence: 99%
“…Wnt7b is a Wnt family ligand important for the proper formation of a number of organs and tissues including the placenta, the eye, the bones, the lungs, the kidney, the central nervous system (CNS), neurons, hair, the pancreas, and olfactory receptor neuron axon connectivity. 70,166,[168][169][170][172][173][174][175][176][177][178][179][180][181][182] Notably, Wnt7b has been reported to regulate vasculature development in the eyes, the brain, and the lungs, by different cellular mechanisms. In the eye, it signals to the endothelial cells of the hyaloid vasculature and activates their apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…70,166,[168][169][170][172][173][174][175][176][177][178][179][180][181][182] In the kidney, Wnt7b is required for renal medulla formation. It promotes LOH elongation, regulates oriented cell division and elongation of the UB epithelium, inhibits proliferation in the peri-UB vasculature, and promotes peri-UB capillary formation.…”
Section: Introductionmentioning
confidence: 99%